Peculiarities of Assessing the Efficiency of Research Organization Divisions - E. A. Grigoreva; N. M. Pahnovskay (Вестник Российского экономического университета имени Г. В. Плеханова)
Nowadays when requirements to effectiveness and productivity become more and more tough, analysis of ways and methods of assessing the efficiency of research divisions gains in importance. Quantitative analysis is one of simple and frequently used approaches to estimating efficiency of organization and its divisions work. It is based on calculation of traditional indices and studying their dynamics for a certain period of time. Practice shows that within the frames of quantitative analysis indices of liquidity, finance stability, business activity and profitability are estimated. However, in view of work specificity, goals of analysis and mentality of finance manager the list of indicators shall be prolonged. For complex assessing research organizations quantitative analysis can be supplemented by qualitative one. Only in this case information can show the real situation in the organization and its divisions.